Efficacy and feasibility of Apatinib and S-1 as a novel oral induction therapy in locally advanced head and neck squamous cell carcinoma: an exploratory phase 2 open-label, single-arm trial - Jiang, Wen; Li, Rongrong; Zhang, Lin; Dou, Shengjin; Ye, Lulu; Shao, Ziyang; Wu, Sicheng; Dong, Minjun; Li, Jiang; Zhu, Guopei (Frontiers in Oncology, 2023)
Objectives: The current standard nonsurgical treatment for locally advanced head and neck squamous cell cancer (LA-HNSCC) is concomitant chemoradiotherapy (CRT). Neoadjuvant chemotherapy combined with CRT has been explored in HNSCC patients and is an acceptable strategy. However, the occurrence of adverse events (AEs) restricts its application. We conducted a clinical study to explore the efficacy and feasibility of a novel induction therapy with orally administered apatinib and S-1 in LA-HNSCC. Materials and Methods: This nonrandomized, single-arm, prospective clinical trial included patients with LA-HNSCCs. The eligibility criteria included histologically or cytologically confirmed HNSCC, with at least one radiographically measurable lesion detected by magnetic resonance imaging (MRI) or computerized tomography (CT) scan, age 18–75 years, and a diagnosis of stage III to IVb according to the 7th edition of the American Joint Committee of Cancer (AJCC). Patients received induction therapy with apatinib and S-1 for three cycles (3 weeks/cycle). The primary endpoint of this study was the objective response rate (ORR) to induction therapy. The secondary endpoints included progression-free survival (PFS), overall survival (OS), and AEs during induction treatment. Results: From October 2017 to September 2020, 49 patients with LA-HNSCC were screened consecutively and 38 were enrolled. The median age of the patients was 60 years (range, 39-75). Thirty-three patients (86.8%) had stage IV disease according to the AJCC staging system. The ORR after induction therapy was 97.4% (95% confidence interval [CI]: 86.2%-99.9%). The 3-year OS rate was 64.2% (95% CI: 46.0%-78.2%) and 3-year PFS was 57.1% (95% CI: 40.8%-73.6%). The most common AEs during induction therapy were hypertension and hand-foot syndrome, which were manageable. Conclusion: Apatinib combined with S-1 as novel induction therapy for LA-HNSCC patients resulted in a higher-than-anticipated ORR and manageable adverse effects. With the associated safety profile and preferable oral administration route, apatinib combined with S-1 is an attractive exploratory induction regimen in outpatient settings. However, this regimen failed to show a survival benefit.